A CSA-Secure Multi-Secret Sharing Scheme in the Standard Model. Issue 1 (2nd January 2020) - Mashhadi, Samaneh
Abstract: In a multi-stage secret sharing (MSSS) scheme, a dealer D share l secrets among the participants in such a way that secrets are reconstructed one by one in different stages. Recently, we proposed a secure MSSS in the standard model. In this paper, we present another MSSS scheme that has shorter public outputs and better security relation with the underlying symmetric encryption in the standard model.